2016
DOI: 10.1111/cas.13003
|View full text |Cite
|
Sign up to set email alerts
|

Unfavorable neuroblastoma prognostic factor NLRR2 inhibits cell differentiation by transcriptional induction through JNK pathway

Abstract: The novel human gene family encoding neuronal leucine rich repeat (NLRR) proteins were identified as prognostic markers from our previous screening of primary neuroblastoma (NB) cDNA libraries. Of the NLRR gene family members, NLRR1 and NLRR3 are associated with the regulation of cellular proliferation and differentiation, respectively. However, the functional regulation and clinical significance of NLRR2 in NB remain unclear. Here, we evaluated the differential expression of NLRR2, where high expressions of N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 37 publications
(97 reference statements)
0
15
0
Order By: Relevance
“…A few of our KO lines target genes having human orthologs that share a GWAS BMI cluster with other genes linked to obesity. Genes for the kinase Dgkg 188 and the neuronal membrane protein Lrrn2 189 have no publicly available KO data or published links to obesity despite having increased body fat in our HTS ( Table 7 ). DGKG and ETV5 (ETS variant transcription factor 5) are the only genes sharing a BMI cluster on human chromosome 3, while LRRN2 and MDM4 (MDM4 regulator of p53) are the only genes sharing a BMI cluster on human chromosome 1 ( Table 8 ); the low body fat observed in Etv5 KO mice 190 and Mdmx KO mice 191 suggests that one or both genes in each of these two BMI clusters may contribute to the GWAS signal.…”
Section: Resultsmentioning
confidence: 99%
“…A few of our KO lines target genes having human orthologs that share a GWAS BMI cluster with other genes linked to obesity. Genes for the kinase Dgkg 188 and the neuronal membrane protein Lrrn2 189 have no publicly available KO data or published links to obesity despite having increased body fat in our HTS ( Table 7 ). DGKG and ETV5 (ETS variant transcription factor 5) are the only genes sharing a BMI cluster on human chromosome 3, while LRRN2 and MDM4 (MDM4 regulator of p53) are the only genes sharing a BMI cluster on human chromosome 1 ( Table 8 ); the low body fat observed in Etv5 KO mice 190 and Mdmx KO mice 191 suggests that one or both genes in each of these two BMI clusters may contribute to the GWAS signal.…”
Section: Resultsmentioning
confidence: 99%
“…Activation of JNK, one of the MAPK members, contributes to apoptosis and tumor progression in conjunction with a variety of stimuli, indicating the contradictory functions of JNK [42][43][44]. Several papers suggested a critical role of JNK activation in malignancy and the poor prognosis of cancer patients [45,46]. The differential roles of JNK activation in MTA-induced anticancer effects were previously reported.…”
Section: Discussionmentioning
confidence: 93%
“…The role of the PI3K/mTOR/Akt pathway in neuroblastoma pathogenesis has been well established, 47 and early-phase clinical trials evaluating the efficacy of inhibitors of PI3K/mTOR/Akt signalling have demonstrated efficacy in children with neuroblastoma. 48 52 The role of signalling through the Fos/Jun pathway in neuroblastoma pathogenesis is less well understood, although recent studies have identified a role for Jun kinase (JNK) signalling in neuroblastoma differentiation, 53 and computational models of neuroblastoma demonstrated an association between JNK signalling and patient survival. 54 The efficacy of inhibition of these pathways in other adult and paediatric cancer models has not previously been reported, and the specific roles of these pathways in the responses of neuroblastoma cells to regorafenib are unknown.…”
Section: Discussionmentioning
confidence: 99%